PENGARUH GREEN INNOVATION, DIGITAL MARKETING, DAN KNOWLEDGE MANAGEMENT TERHADAP SUSTAINABILITY BUSINESStPADA PT. HATTENtBALI - Putu Purnama Dewi; I Gusti Ngurah Putra Sudhiksa (Media Bina Ilmiah, 2022)
This studyaaims to determineathe effect of green innovation, digital marketing, knowledge management partially on business sustainability. Green innovation is a means by which companies eliminate or minimize theanegative impact of their operations on the environment, digital marketing is a medium used as an application to build a brand image of a company or product and encourage sales functions to target consumers, and knowledge managementatis a systematicatcoordination in organizations that can manage human resources (HR), processes,atechnology, and organizational structures that can increase value through innovation and reuse. The population uses employees of PT. Hatten BaIi with samples taken as many asr71 people. The data were analyzedrby using several technques such as Validity Test,aReliability Test,rClassic AssumptionrTest,rMultiple LineartRegression Analysis,rDeatemination Coefficient Test, and t Test.rFrom the research results obtained the results: (1) green innovation has a significanttpositive effect on businesstsustainability. (2) digital marketing has a significantrpositive effectton businessrsustainability. (3) knowledge managementrhas a significantrpositivereffect on businessrsustainability. The independent variable has a large effect on businessrsustainability by 62.8%. The suggestions that researchers can give are for PT. Hatten Bali needs to improve the quality of implementing green innovation, digital marketing, and knowledge management to improve the company's sustainability